Synthesis, structure and conformational mobility of tetra-substituted cyanomethoxy p-tert-butylcalix[4]arenes. Issue 43 (14th April 2016) - D'Alessio, Daniel; Krause-Heuer, Anwen M.; Skelton, Brian W.; Fraser, Benjamin H.; Massi, Massimiliano; Ogden, Mark I.
Abstract : A range of p-tert -butylcalix[4]arenes are functionalized at the lower rim with nitrile and amide functional groups, and the conformational mobility of macrocycles is investigated. Abstract : The syntheses and single crystal X-ray structure determinations of 5, 11, 17, 23-tetra- tert -butyl-25, 26, 27, 28-tetrakis(cyanomethoxy)calix[4]arene (partial-cone conformer), 5, 11, 17, 23-tetra- tert -butyl-25, 27-bis(diethylcarbamoylmethoxy)-26, 28-bis(cyanomethoxy)calix[4]arene (cone and partial-cone conformers), 5, 11, 17, 23-tetra- tert -butyl-25, 26, 27-tris(cyanomethoxy)-28-hydroxycalix[4]arene, and 5, 11, 17, 23-tetra- tert -butyl-25-diethylcarbamoylmethoxy-26, 27, 28-tris(cyanomethoxy)calix[4]arene (cone conformer) are reported. The calixarenes are found to be conformationally mobile when heated in DMSO, favouring the partial-cone conformer at equilibrium. The tris-substituted cyanomethoxy derivative was found to assume the partial-cone conformation in the solid state. Attempts to convert nitrile groups to tetrazole moieties in derivatives containing both amide and nitrile groups were unsuccessful.